Measuring the effectiveness of intermediary loyalty programmes in the motor insurance industry: Loyal versus non-loyal customers - Manuel Leiria; Efigénio Rebelo; Nelson de Matos (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - The insurance industry has not been able to effectively retain its customers and struggles to establish and maintain long-lasting relationships with them. The purpose of this paper is thus to identify the main factors that explain the cancellation of motor insurance policies by individual customers, considering the influence of intermediaries on their decisions. Design/methodology/approach - The data used in this research is based on a sample of 3,500 insurance policies that lapsed during the period of analysis between January and July 2017, against another sample of 3,500 policies that did not lapse, from a major insurance company in Portugal. Binary logistic regression was used for data analysis, using IBM SPSS software. Findings - Aggressive tactics by insurance companies for customer acquisition may induce the cancellation of insurance policies. More valuable customers, the policies with higher premiums and recent claims, as well as the ancillary intermediaries and agents, are determinants of insurance cancellation. Conversely, the payment of policies by direct debit and without instalments reduces the probability of cancellations. Research limitations/implications - The main limitation of this study is the restriction on data access. Insurance companies are significantly resistant to sharing their customer data - including with academic researchers - even in an anonymised form. Practical implications - The paper highlights internal and external practices of insurance companies that should be reformulated to significantly improve their performance regarding product cancellation, related to customer information management, mistrust behaviours related to stakeholders and new value propositions that deepen the relationships with intermediaries. Originality/value - This research developed a framework with which to identify the factors that are mainly associated with motor insurance cancellation and to predict its likelihood.
Keywords: 650; Customer retention; Intermediary; Motor insurance; Product cancellation